2013
DOI: 10.1120/jacmp.v14i2.4022
|View full text |Cite
|
Sign up to set email alerts
|

A study of longitudinal tumor motion in helical tomotherapy using a cylindrical phantom

Abstract: Tumor motion during radiation treatment on a helical tomotherapy unit may create problems due to interplay with motion of the multileaf collimator, gantry rotation, and patient couch translation through the gantry. This study evaluated this interplay effect for typical clinical parameters using a cylindrical phantom consisting of 1386 diode detectors placed on a respiratory motion platform. All combinations of radiation field widths (1, 2.5, and 5 cm) and gantry rotation periods (16, 30, and 60 s) were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…5) As a result of this study, 5 cm of field width exhibited better gamma passing rates than 1 cm and 2.5 cm widths in the gamma comparisons with 2% dose discrepancy and 2 mm distance-to-agreement. In a different study focused on couch motion, 7) the couch motion was varied within a range of values, and the effects on the dose profiles were assessed.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…5) As a result of this study, 5 cm of field width exhibited better gamma passing rates than 1 cm and 2.5 cm widths in the gamma comparisons with 2% dose discrepancy and 2 mm distance-to-agreement. In a different study focused on couch motion, 7) the couch motion was varied within a range of values, and the effects on the dose profiles were assessed.…”
Section: Introductionmentioning
confidence: 72%
“…[1][2][3] The motion-induced dose error presents additional complications in helical tomotherapy, as the tumor motion interacts with the couch motion. 4,5) Owing to the tumor motion, the treatment field does not reach the tumor region constantly, and repeatedly shifts in and out of the tumor area. 6,7) This effect prevents the delivery of the planned dose to the tumor region.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have noted that lung respiratory motion was predominant (though not exclusively) in the patient superior–inferior (SI) direction. 8 , 9 Thus, for simplicity, we assumed in this study that (1) the organ motion was uniform along 1-dimensional (SI) direction and (2) the anatomical structures (both tumor and MD) were rigid with no deformation.…”
Section: Methodsmentioning
confidence: 99%
“…For hypofractional treatment such as SBRT for lung tumors, the helical tomotherapy unit has advantages but also causes some concerns: as advantages, conformal delivery by IMRT and precise set-up using the onboard MVCT system [ 4 ]; as concerns, expansion of the low-dose irradiated lung volume caused by the multidirectional and coplanar delivery method, and a discrepancy between calculated and delivered dose distributions due to movements of tumors and mechanical dynamics peculiar to helical tomotherapy: motions of the multileaf collimator, gantry rotation, and couch translation through the gantry. Despite these concerns, several experimental studies have shown that efforts to restrict respiration-associated tumor motion and optimize the planning target volume (PTV) margin lead to an acceptable minimal dose error [ 5 7 ], and a number of clinical reports on HT-SBRT have demonstrated its feasibility, with a promising outcome and favorable tolerance [ 4 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%